2008
DOI: 10.1007/s10666-008-9168-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Competitive Sorption Process of Multiple Solutes During their Transport in Porous Media

Abstract: A general mathematical model to solve the advection-dispersion transport equation for multiple solutes was developed, where the dual porosity mobile-immobile mass transfer, the two-site non-equilibrium model and firstorder transformation reactions were included. The two-site model was expressed with an equilibrium sorption term and a kinetic term. One of three kinetic models could be used: the non-linear, the bilinear and the pore diffusion model. The traditional Freundlich or Langmuir isotherms were employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…Multiple studies have established a linear relationship between pore water velocity and ω [45,65,66]. Solute transport for PNE and CNE was simulated by Avila and Breiter [67] using f m = 0.88 and f em = 0.5. Additionally, Köhne et al [68] found that, for pesticide transport studies, fitting f m = 0.258 using an inverse DP two-site sorption model yielded the best match for breakthrough.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have established a linear relationship between pore water velocity and ω [45,65,66]. Solute transport for PNE and CNE was simulated by Avila and Breiter [67] using f m = 0.88 and f em = 0.5. Additionally, Köhne et al [68] found that, for pesticide transport studies, fitting f m = 0.258 using an inverse DP two-site sorption model yielded the best match for breakthrough.…”
Section: Discussionmentioning
confidence: 99%